Impact Of Marketing Mix And Service Quality On Patient Satisfaction Through Patient Loyalty - Marolop Bungaran Tua Situmorang; Dwi Cahyono; Diyah Probowulan (UNIVED Press, 2025)
This study investigates the effects of the marketing mix and service quality on patient satisfaction and loyalty at RSUD dr. Soebandi, a government run hospital in Kabupaten Jember. Utilizing a quantitative research design, the study involved a sample of 200 inpatient patients, selected through stratified random sampling to ensure representation across different care classes. Data were collected via surveys measuring perceptions of marketing mix elements (product, price, place, promotion, people, process, and physical evidence) and service quality (reliability, responsiveness, assurance, empathy, and tangibles). The findings reveal that both the marketing mix and service quality have a significant positive impact on patient satisfaction and loyalty, with patient loyalty acting as a mediator between these variables and satisfaction. The study highlights the importance of improving service quality and strategically applying the marketing mix to foster long-term patient loyalty, providing valuable insights for hospital management in a competitive healthcare environment.